Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

4x + 2y=4 and 3x -y= -7

Sagot :

Answer:

y =  4

x = -1

Step-by-step explanation:

4x + 2y = 4     Eq. 1

3x - y = -7       Eq. 2

from the  Eq. 2

3x = y - 7

3x + 7 = y        Eq. 3

Replacing the value of the Eq. 3 in the Eq. 1

4x + 2(3x+7) = 4

4x + (2*3x + 2*7) = 4

4x + (6x + 14) = 4

10x + 14 = 4

10x = 4 - 14

10x = - 10

x = -10/10

x = -1

from the Eq. 3

3x + 7 = y

3*-1 + 7 = y

-3 + 7 = y

4 = y

Check:

from the Eq. 1

4x + 2y = 4

4*-1 + 2*4 = 4

-4 + 8 = 4